2008
DOI: 10.4161/chan.2.3.6385
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity at the Water-Hydrocarbon Core Interface of the Membrane: Consequences on the Nicotinic Acetylcholine Receptor

Abstract: Almost all lipid-exposed transmembrane domains of integral proteins contain aromatic residues flanking the hydrophobic segment of the domains. These residues generally reside close to the carbonyl region of the membrane, and several structural and functional roles have been associated to these residues. Although the roles and physicochemical reasons for aromatic preference have been extensively studied using model systems, few studies have been done in a native membrane system. To gain insight about the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…; Wallace and Janes ; Lizardi‐Ortiz et al . ). We reviewed the validity of these observations for the annotated human proteome, and for a set of 220 synaptic membrane proteins, and we found that the accumulation of tyrosine and tryptophan was in fact a global feature of their transmembrane domains (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…; Wallace and Janes ; Lizardi‐Ortiz et al . ). We reviewed the validity of these observations for the annotated human proteome, and for a set of 220 synaptic membrane proteins, and we found that the accumulation of tyrosine and tryptophan was in fact a global feature of their transmembrane domains (Table ).…”
Section: Discussionmentioning
confidence: 97%